Mapping of the binding sites of human diamine oxidase (DAO) monoclonal antibodies - Schwelberger, Hubert G. (Inflamm Res, 2017)
OBJECTIVE: Recently we characterized five mouse monoclonal antibodies that allow the specific and sensitive detection of human diamine oxidase (DAO). To understand differences in binding characteristics and recognition of enzyme variants, we mapped the antibody binding sites. METHODS: Fragments of human DAO were expressed as glutathione-S-transferase fusion proteins that were used for testing antibody binding on immunoblots. Combined information from species cross-reactivity, sequence comparison and binding site-prediction software were used to localize the epitope recognized by each antibody. RESULTS: All five monoclonal DAO antibodies bound to linear epitopes between the N3 and enzymatic domains of the 732 amino acid protein. The binding sites could be mapped onto amino acid regions V(262)-E(278) and P(279)-R(288), respectively, which exhibit considerable sequence variation in mammals explaining the fact that the human DAO antibodies do not cross-react with DAO from other species. The antibodies efficiently bind only denatured human DAO but not the native protein. CONCLUSIONS: Characterization of the binding sites of the DAO antibodies revealed that the antibodies bind two adjacent epitopes and exhibit similar binding characteristics and species cross-reactivity. As the epitopes do not overlap any of the amino acid substitutions described for clinically significant DAO gene polymorphisms, our antibodies will also be useful for analyses of the mutant DAO proteins.